Dietary impact of Ocimum tenuiflorum leaf extract on the growth metrics and immune responses of shrimp (Penaeus monodon) against white spot syndrome virus (WSSV) - Md Rejwanul Haque Galib; Alokesh Kumar Ghosh; Wasim Sabbir (Heliyon)
The present study was conducted to evaluate the efficacy of Ocimum tenuiflorum extract against the white spot syndrome virus (WSSV) in black tiger shrimp (Penaeus monodon) following oral administration in vivo. The methanol extract derived from the extraction was sprayed into feed at a concentration of 0.0 %, 0.05 % and 0.1 %. The feeding trial was continued for four weeks, following which the shrimps were injected with WSSV and mortality was checked two weeks after the trial. The findings revealed that shrimp fed with extract had significantly improved (p < 0.05) growth parameters (weight gain, specific growth rate) and feed utilization efficacy (less feed conversion ratio, high protein efficiency ratio) compared to the control group. The extract improved the immunity of shrimp significantly, as demonstrated by increased immunological parameters including total haemocyte count, prophenoloxidase activity, superoxide dismutase activity and up regulation of immune-related genes, which ultimately increased the disease resistance capability in Penaeus monodon against WSSV. Based on the experiment, 0.1 % extract had the highest growth and immune response against WSSV followed by Treatment 1 and control. Therefore, the extract of Ocimum tenuiflorum could be used as an immunostimulant with feed to boost the growth and resistance capacity of shrimp against WSSV as well as for the sustainable production of shrimp.